Manajemen Sarana Dan Prasarana Pendidikan Untuk Meningkatkan Mutu Pembelajaran Di Sekolah - Sari Nusantara Putri (Thawalib: Jurnal Kependidikan Islam, 2023)
The aim of the research is to describe the management of educational facilities and infrastructure to improve the quality of learning at Pamekasan 6 State Junior High School. The research method is qualitative through a case study approach. Data collection techniques: interviews, observation, and documentation. Data processing techniques: reduction, data presentation, and conclusion. Wetness engineering data: credibility and confirmability. The research results show: (1) planning: collecting analysis of facility and infrastructure needs. (2). Procurement: purchasing items that prioritize learning needs. (3) inventory: recording goods in the inventory book. (4) maintenance: cleaning classroom facilities and building maintenance. (5) removal: throwing away items that are unfit and do not meet the criteria.